Global mapping of open access literature availability in the area of scientometrics research during 2012-2021 / Maya Deori ... [et al.] - Deori, Maya; Emami, Maryam; Verma, Manoj Kumar; Che Daud, Suriana (Faculty of Information Management, 2022)
Open access publishing has received considerably a greater amount of recognition in the sector of scholarly communication by highlighting the significant advantages of creating impactful literature. The present study aims to identify the availability of open access literature in scientometrics and visualize the adoption of open access publishing by comparing various sectors of bibliographic information between open access and non-open access literature. Performance measurement and network visualization of the Scientometrics mapping method have been used. The study highlights that the OAP ratio is relatively low in the area of scientometrics yet has a higher average citation value than non-open access publications. China is the most productive country to adopt OA publishing however have low collaborative network than the United States and the United Kingdom. Based on the importance of Scientometrics studies, the contributors should adopt open access publishing to enhance the visibility and exposure of the quality of research globally.